ANALISIS PARTISIPASI PEREMPUAN STUDI KASUS DI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN KERINCI: NANIK MANDASARI, S.IP, M,Si - nanik mandasari (JURNAL ADMINISTRASI NUSANTARA, 2020)
Title. Analysis of Women's Participation Case Study in the Kerinci Regency Regional House of Representatives (DPRD). This research was carried out in the Kerinci Regency Regional House of Representatives (DPRD). Women's participation in the Kerinci Regency Regional Representative Council (DPRD) in the election of DPRD members has not participated maximally because only one female DPRD member is elected because women's participation is not as optimal as men's women's space and time limitations in entering politics there are still half measures and voters do not understand and know for sure the female candidates they have chosen. The research problem formulation is, What is the Participation of Women in the Kerinci Regency Regional Representative Council (DPRD)? The research objective is to find out the participation of women in the Kerinci Regency Regional Representative Council (DPRD). This research uses a qualitative approach where data is obtained through field interview guidelines for 5 informants referring to 6 research indicators namely 1. Formal education 2. Organizational Experience 3. Recruitment System 4. Social and Religious Perception 5. Cultural Perception 6. Cultural Perception. The data obtained in the field were analyzed based on the classification of the informant's answers described in the results and discussion of the study which was then interpreted by the researcher. it is known that Women's Participation in the Kerinci Regency Regional Representative Council (DPRD), for indicators one to six has not been carried out to the maximum that is women's participation in the Kerinci Regency Regional Representative Council (DPRD) has not been able to represent the number of women in the Kerinci Regency because women are elected in the Kerinci Regency Regional Representative Council (DPRD), only one person. For this reason, the writer suggests that the participation of women in the Kerinci Regency Regional Representative Council (DPRD) can be increased and the number is higher and women in the Kerinci Regency choose female candidates so that women's participation in the Kerinci Regency Regional Representative Council (DPRD) can contribute. in the development of the Kerinci Regency.